2006
DOI: 10.1080/09670260500505524
|View full text |Cite
|
Sign up to set email alerts
|

Scale of impact determines early post-disturbance assemblage structure in subtidalFucusbeds in the Baltic Sea (Bornholm, Denmark)

Abstract: Disturbances occasionally create gaps of varying sizes in the canopy cover of macroalgae on temperate reefs. This study quantified the size distribution of naturally occurring gaps in a subtidal Fucus serratus canopy, and experimentally tested the hypotheses that (i) early post-disturbance abundance of dominant assemblage-formers in the canopy-dominated habitat will depend on the spatial extent of the impact, and (ii) the effects of disturbance on the abundance of dominant assemblageformers at the edges of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…At the warmest location, the lack of response could partly be explained by low propagule supply (there were no fucoids in the control plots) and partly be related to competition from rapidly colonizing turfs. Other studies have shown rapid colonization of turf into disturbed plots and subsequent inhibition of fucoid settlement, survival and growth (Isaeus et al 2004, Wernberg 2006. It is, of course, possible that fucoids, over time, eventually would establish into these plots (Edwards 1998, Worm et al 2001, Eriksson & Johansson 2003.…”
Section: Local-scale Disturbance Effects: Functional Groups Expected mentioning
confidence: 96%
See 3 more Smart Citations
“…At the warmest location, the lack of response could partly be explained by low propagule supply (there were no fucoids in the control plots) and partly be related to competition from rapidly colonizing turfs. Other studies have shown rapid colonization of turf into disturbed plots and subsequent inhibition of fucoid settlement, survival and growth (Isaeus et al 2004, Wernberg 2006. It is, of course, possible that fucoids, over time, eventually would establish into these plots (Edwards 1998, Worm et al 2001, Eriksson & Johansson 2003.…”
Section: Local-scale Disturbance Effects: Functional Groups Expected mentioning
confidence: 96%
“…30% increase in turf cover and partial canopy loss also increased turfs, but to a lesser extent. Previous studies have shown that increases in resource availability, such as light, nutrients and space, promote rapid colonization by turf (Johnson & Mann 1993, Worm et al 2001, Connell 2005, Wernberg 2006, Russell 2007, Antoniadou et al 2010. However, in contrast to our findings, and those of Wernberg & Connell (2008) in South Australia where turfs also increased in partial clearings, turfs only increased after complete kelp removal in Tasmania (Flukes et al 2014).…”
Section: Local-scale Disturbance Effects: Functional Groups Expected mentioning
confidence: 99%
See 2 more Smart Citations
“…The overall biogenic habitat structure of each reef was quantified by running ten 25 m transects along haphazard compass bearings and recording the distances (to nearest 10 cm) of habitat change. This technique has previously been successfully applied to describe habitat structure in algal dominated assemblages in other subtidal habitats (Kennelly 1987, Wernberg 2006, Connell & Irving 2008. We distinguished between four major habitat types: (1) mono-specific kelp canopy (>90% Ecklonia radiata), 2fucalean canopy (>50% fucalean algae), (3) mixed kelp and fucalean canopy (50-90% kelp and 10-50% fucalean algae) and (4) canopy-free areas (gaps of < 10% canopy algae), typically dominated by small foliose red algae (<25 cm) (e.g., Hennedya crispa) or articulated coralline algae (e.g., Amphiroa anceps).…”
Section: Habitat Structurementioning
confidence: 99%